PROJECT-BASED LEARNING STRATEGIES TO ENHANCE COGNITIVE DEVELOPMENT AND HOT SKILLS IN EARLY CHILDHOOD - Upik Elok Endang Rasmani; Yuanita Kristiani Wahyu Widiastuti; Putri Agustina (Universitas Panca Sakti Bekasi, 2024)
This research aims to describe project-based learning strategies to improve cognitive development and HOTS skills in early childhood. The research method used is the systematic literature review method. The data collection technique is done by collecting reference articles related to project learning to improve early childhood cognitive development and HOTS skills. The results showed that project-based learning strategies can enhance early childhood cognitive development and HOTS skills. The project-based learning process involves planning, implementation, and evaluation stages. Children can determine project topics, gather information, create products, and present project results. Children can develop critical, creative, collaborative, and communicative thinking skills through project-based learning strategies. This research contributes to developing early childhood curricula and learning practices that meet the needs of the 21st century